The Multiple intelligences Strategy into Students’ Reading Comprehension Mastery at eleventh grade students’ of SMA Swasta HKBP Sidorame - Pakpahan, Carolina (ELT (English Language Teaching Prima Journal), 2023)
This study deals with the effort of finding the effect of the Multiple Intelligences Strategy on the students’ reading comprehension Mastery. This study was conducted by using experimental quantitative research. The objective of this study is to find out whether Multiple Intelligences Strategy affects students’ reading comprehension mastery or not. There were 60 students used as the sample of this research who came from eleventh-grade students’of Accounting (AK) major in SMA Swasta HKBP Sidorame. The sample of this research was divided into two groups namely experimental group XI IPA consists 30 students and control group XI IPS consists of 30 students. The experimental group was taught by using Multiple Intelligences Strategy and the control group was taught by using Conventional Method namely Direct Instruction Strategy. The instrument used for collecting the data that was tested in the form of multiple choices with a total number of 25 questions. The test was divided into pre-test and post-test. The data was analyzed by using a t-test formula to see whether the Multiple Intelligences Strategy significantly affects students’ reading comprehension or not. The result of the analysis shows that the t-observed (3.33) is higher than the t-table (1.671) with a level of significance (0.05) and the degree of freedom (df= 58). The result of the analysis shows that the hypothesis of the study is accepted. It can be concluded that Multiple Intelligences Strategy affects students’ reading comprehension. In this study, the writer suggests that teachers should be able to use Multiple Intelligences strategies as an alternative in the teaching process for improving and creating enjoyable learning experiences, especially reading comprehension. Keywords: Multiple Intelligences, Reading Comprehension, Strategy